2019
DOI: 10.24198/jkp.v7i3.1175
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients, Self-Efficacy and Quality of Life among Patients with Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus as a chronic disease requires a long-term care, which influence the quality of life (QOL). A mechanism perceived by the patients who engage in long-term treatment, such as self-efficacy (SE) is prerequisite for the success of disease management. The study aimed to identify the relationship between characteristics of patients, SE and domains of QOL among patients with type 2 diabetes mellitus (T2DM) living in community.The study used a correlational analytical with a cross-sectional approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…After removing duplicates, 1557 records were screened by title and abstract and 191 full-text articles were assessed for eligibility. Five additional records were identified through manual searches ( 50 , 80 ) and citation list ( 62 , 104 , 110 ). Seventy-one studies were finally included: sixty-one cross-sectional studies ( 34 , 35 , 44 , 45 , 47 69 , 71 78 , 80 , 83 – 88 , 91 – 97 , 99 – 102 , 104 111 ), five observational prospective studies ( 36 , 70 , 81 , 82 , 89 ), four randomized controlled trials (RCTs) ( 79 , 90 , 98 , 103 ) and one pre-post intervention study ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates, 1557 records were screened by title and abstract and 191 full-text articles were assessed for eligibility. Five additional records were identified through manual searches ( 50 , 80 ) and citation list ( 62 , 104 , 110 ). Seventy-one studies were finally included: sixty-one cross-sectional studies ( 34 , 35 , 44 , 45 , 47 69 , 71 78 , 80 , 83 – 88 , 91 – 97 , 99 – 102 , 104 111 ), five observational prospective studies ( 36 , 70 , 81 , 82 , 89 ), four randomized controlled trials (RCTs) ( 79 , 90 , 98 , 103 ) and one pre-post intervention study ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies ( n = 5,005) ( 44 46 , 49 , 51 , 52 , 56 , 68 , 70 , 72 , 74 , 79 , 81 , 82 , 84 , 85 , 91 , 95 , 98 – 100 , 104 ) evaluated the relationship between empowerment-related constructs and general QoL in patients with T2DM. Specific patient empowerment scales were used in six studies ( 44 46 , 49 , 51 , 52 ) while self-efficacy was used in the remaining sixteen studies ( 56 , 68 , 70 , 72 , 74 , 79 , 81 , 82 , 84 , 85 , 91 , 95 , 98 – 100 , 104 ). One study ( 44 ) used ANOVA to quantify this association and was not included in the MA.…”
Section: Resultsmentioning
confidence: 99%
“…Peters et al (2019) researched medical case patients and reported that individuals with low self-efficacy and a higher disease burden tend to have a lower quality of life. Additionally, research by Winahyu et al (2019) on diabetes Mellitus patients showed a significant relationship between self-efficacy and quality of life domain. It was observed that increased perceived selfefficacy among patients was associated with higher scores in quality of life domain.…”
Section: Path Coefficientmentioning
confidence: 97%
“…Penelitian ini di dukung juga oleh (Dionita, 2016) menunjukan hasil signifikasi (p=0,334) serta (p=0,105) pada hubungan efikasi diri dan aktifitas fisik bahwa tidak terdapat hubungan antara efikasi diri dengan aktifitas fisik. Namun, penelitian saat ini tidak konsisten dengan studi terdahulu pada klien dengan penyakit kronik lain (Winahyu et al, 2019).…”
Section: Tabel 2 Efikasi Diri Dan Gaya Hidup Lansia Hipertensiunclassified